2014
DOI: 10.4028/www.scientific.net/amm.574.109
|View full text |Cite
|
Sign up to set email alerts
|

Double Wishbone Independent Suspension Parameter Optimization and Simulation

Abstract: The wheeled armoredvehicle double wishbone independent suspension system, established the double wishbone suspension arm model, and optimized analysis. Optimization results show that: the suspension parameters optimization design, the front suspension performance has been greatly improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Since the year 2000, some conference papers focus on small but specific studies; Wang et al [1] explored kinematics characteristics of suspension with double trailing arms for light off-road vehicles; they found that the double trailing arm lengths, the angles between double trailing arms, horizontal/vertical plane, and bushing stiffness of the double trailing arms linking with frame are four major parameters that affect the caster and front-wheel steering angle. Tian et al [2] optimized analysis of the wheeled armored vehicle double wishbone independent suspension system. Guo and Sun [3] simulated model of the double wishbone independent front suspension with a single degree of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…Since the year 2000, some conference papers focus on small but specific studies; Wang et al [1] explored kinematics characteristics of suspension with double trailing arms for light off-road vehicles; they found that the double trailing arm lengths, the angles between double trailing arms, horizontal/vertical plane, and bushing stiffness of the double trailing arms linking with frame are four major parameters that affect the caster and front-wheel steering angle. Tian et al [2] optimized analysis of the wheeled armored vehicle double wishbone independent suspension system. Guo and Sun [3] simulated model of the double wishbone independent front suspension with a single degree of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…Інтенсивні пошукові дослідження в цьому напрямку ведуться у багатьох країнах світу [2,[5][6][7][8][9][10][11].…”
unclassified